Trust and distrust in the resolution of protracted social conflicts: the case of Colombia - Filippidou, Anastasia; O’Brien, Thomas (Taylor and Francis, 2020)
In protracted social conflict, trust between the contending parties is absent and distrust can prevent or undermine attempts to find a sustainable resolution. It is important to recognise distrust as an active process, distinct from low trust or the absence of trust. Previous work has identified the difference between thick (internal) and thin (social) trust bonds within and between groups. Recognising the varied nature of trust and distrust can provide opportunities to create mechanisms to bridge divides. It may be possible to create institutions able to guarantee agreements, as leading actors persuade followers by calling on thick trust. This paper examines the negotiation of the peace agreement between the Government of Colombia and the FARC, following more than 50 years of conflict. The aims of the paper are to (1) identify the form and extent of trust and distrust between parties, and (2) determine how distrust was managed in negotiating the peace agreement. The findings point to the ability of elite actors to develop thin trust through repeated formal interactions and in turn use thick trust to bind followers
Keywords: identity; conflict resolution; distrust; trust; FARC; Colombia